The awareness and use of online database among political science students - Osman, Zuraini; Othman, Roslina (IIUM Press, 2011)
This paper reports on the awareness and use of online database among political science students. They faced the discomfort of reading from the screen or poor graphic quality and they prefer to print out articles for reading and do most of their reading from the paper printout. Besides, they also prefer PDF format for printing, although the HTML format is better for skimming. The users may be unaware of relevant resources in the library collection. As faculty members reported never using electronic journals; the reasons cited were unfamiliarity with how to access the journals. They had never accessed computer engineering databases available through the library and of those, half had never heard of them. Apart from that, electronic journals are of lower quality than print is another problem that may be diminishing as a high percentage of peer-reviewed journals are digitized. Designing appropriate access policies has become an important issue.